The Origins of Chinese Civilization - Keightley, David N. (Studies on China Series., 2022)
The seventeen contributors to this interdisciplinary volume bring to the study of early China the analytical concerns of archeology, art history, botany, climatology, cultural and physical anthropology, ethnography, epigraphy, linguistics, metallurgy, and political and social history. Readers interested in such topics as the origin of rice or millet agriculture, the origin of writing, the nature of the trie, and the processes of state formation will find much.